Titanium as a Potential Addition for High-Capacity Hydrogen Storage Medium - Filippo Zuliani; Leonardo Bernasconi; Evert Jan Baerends (Journal of Nanotechnology)
We study the adsorption of hydrogen molecules on a titanium atom supported by a benzene molecule using generalized gradient corrected Density Functional Theory (DFT). This simple system is found to bear important analogies with titanium adsorption sites in (8, 0) titanium-coated single-walled carbon nanotubes (SWNTs) (T. Yildirim and S. Ciraci, 2005) In particular, we show that up to four H2 molecules can coordinate to the metal ion center, with adsorption patterns similar to those observed in Ti-SWNTs and no more than one molecule dissociating in the process. We analyze in detail the orbital interactions responsible for Ti-benzene binding and for the electron transfer responsible for the H2 dissociation. We find the latter to involve a transition from a triplet to a singlet ground state as the hydrogen molecule approaches the adsorption site, similar to what has been observed in Ti-SWNTs. The total Ti-H2-binding energy for the first dissociative addition is somewhat inferior (~0.4 eV) to the value estimated for adsorption on Ti-SWNTs. We analyze in detail the orbital interactions responsible for the H2 binding.